Optic nerve sheath fenestration in cryptococcal meningitis - Tatyana Milman (Dove Medical Press, 2008)
Tatyana Milman1, Neena Mirani1,2, Roger E Turbin11Ophthalmology Department, Institute of Ophthalmology and Visual Science, 2Pathology Department, University Hospital, New Jersey Medical School, Newark, NJ, USAAbstract: A patient with acquired immunodeficiency syndrome (AIDS) developed crytpococcal meningitis, complicated by papilledema and severe progressive visual loss despite medical therapy. Bilateral optic sheath fenestration resulted in significant improvement in vision and resolution of papilledema. Histopathologic evaluation of the optic nerve sheath demonstrated numerous cryptococci. Optic nerve sheath fenestration may be an effective treatment method when high intracranial pressure is contributing to visual loss, even in the presence of involvement of the optic nerve sheath by the fungus.Keywords: optic nerve sheath, cryptococcal, meningitis, fenestration